Histomorphological study on the tongue of the duck in the Caribbean with relation to feeding habit - Mohamed, Reda (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study was to give detailed descriptions of the morphological and histological structures of the tongue of the Muscovy duck as it relates to their feeding habit. Materials and Methods: Ten adult Muscovy ducks weighing 2–4 kg were used. The ducks were slaughtered and their oral cavities were opened to detect in situ position of the tongues. Each tongue was dissected and examined grossly. Samples of various parts of the tongue were taken for routine histological examination. Results: The tongue of the Muscovy ducks was distinguished grossly as the apex, body, and root. A dorsal median sulcus, conical papillae, and lingual prominence were observed grossly. Microscopic observations showed the tongue of the Muscovy duck was covered by stratified squamous epithelium; keratinized and non-keratinized. The lamina propria of the tongue contained lingual glands, entoglossum cartilage, lymphoid nodules, as well as blood vessels and nerves. Conclusion: The morphological and histological variations of the tongue of the Muscovy duck may infer that its unique structures are related to their feeding habits. J. Adv. Vet. Anim. Res., 6(1): 74-81, March 2019